How technique modifications in elite 100m swimmers might improve front crawl performances to podium levels: Swimming `Chariots of Fire` - Sanders, R. H.; Takagi, H.; Vilas-Boas, J. P. (Sports Biomechanics, 2021)
In this paper ways in which performance in 100 m front crawl might be improved are explored. Researchers were identified as `primary sources` to provide a rationale for how swimmers might improve their performance and to estimate the potential magnitude of improvement. The researchers selected as the primary sources were identified from an initial search of the Scopus and Web of Science data bases using keywords appropriate for the race phases including start, stroking, turn, and finish and their component sub-phases. Recent research was prioritised to ensure that the latest knowledge was considered. Based on an analogy drawn from the `Chariots of Fire` movie, the hypothetical question was asked: how can we reduce the 100 m time by 0.5s of a swimmer who is already an elite performer? Estimates of potential improvement ranged from 0.013s for the reaction time in the start phase to 1.0s by optimising mid-pool kicking to minimise drag. It is concluded that even at the very elite level, fine-tuning to optimise performance in the different phases of the race could elevate an elite swimmer to podium level performance.